Prevalence of study related anxiety among medical students: a study from a medical college in central Nepal - Bhattarai, Praveen; Joshi, Devavrat; Gurung, Bhupendra Singh (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Medical education can lead to anxiety and depression in medical students which may have negative academic and professional consequences on them. The objective of this study was to find out the prevalence of study related anxiety, its severity and frequency of different symptoms related to anxiety among medical students.Results: Study-related anxiety was found in 73.33% of students. Anxiety was more common amongst final year medical students (83.33%) followed by 1st/2nd year students (76.67%). Prevalence of anxiety was found to be less among 4th-year medical students (63.33%). The majority of the students experienced a mild to moderate level of anxiety. i.e.44.31 % and 36.37 % respectively. The most common symptoms of study related anxiety were recurrent fearful thoughts about studies, constant tension about studies and panic feeling about exam in varying degree of severity.Conclusion: There is a high prevalence of study related anxiety among medical students in the current study. Early identification and timely intervention of study related anxiety symptoms in medical students will prevent mental distress and negative effect on their academic pursuits.